2009
DOI: 10.1289/ehp.0900633
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function and Plasma Concentrations of Polyhalogenated Compounds in Inuit Adults

Abstract: BackgroundSeveral ubiquitous polyhalogenated compounds (PHCs) have been shown to alter thyroid function in animal and in vitro studies. So far, epidemiologic studies have focused on the potential effect of a small number of them, namely, polychlorinated biphenyls (PCBs) and some organochlorines (OCs), without paying attention to other important PHCs.ObjectivesWe investigated the relationship between exposure to several PHCs and thyroid hormone homeostasis in Inuit adults from Nunavik.MethodsWe measured thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(166 citation statements)
references
References 40 publications
9
149
8
Order By: Relevance
“…So far, epidemiologic studies have focused on the potential effect of PFCs on human thyroid functions. Several large-scale surveys of Nunavik permanent residents (Dallaire et al 2009), US. general adult population (Melzer et al 2010), and children living near a chemical plant of USA (Lopez-Espinosa et al 2012) suggested the association of increased serum PFCs with abnormal THs levels and thyroid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…So far, epidemiologic studies have focused on the potential effect of PFCs on human thyroid functions. Several large-scale surveys of Nunavik permanent residents (Dallaire et al 2009), US. general adult population (Melzer et al 2010), and children living near a chemical plant of USA (Lopez-Espinosa et al 2012) suggested the association of increased serum PFCs with abnormal THs levels and thyroid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in other publications that TH concentrations could correlate positively or negatively with PBDE or PCB concentrations, and the actual relationship may be dependent on the exposure level, population characteristics, the specific congeners that are measured, and other study characteristics [79][80][81][82][83].…”
Section: Relationships Between Th Concentrations and Pbde Pcb And Dmentioning
confidence: 99%
“…It has been observed in rats and seals that PCBs can disturb thyroid homeostasis and TH functions [30]. PCBs can also disturb TH homeostasis in humans, but the reports regarding this are few and their results have not been consistent [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies that evaluate associations of PBDEs exposure and thyroid hormones in adults and newborns have been published previously, but their results are not consistent (Hagmar et al, 2001;Mazdai et al, 2003;Herbstman et al, 2008;Turyk et al, 2008;Dallaire et al, 2009;Kim et al, 2009;Roze et al, 2009;Chevrier et al, 2010;Zhang et al, 2010;Chevrier et al, 2011;Eggesbø et al, 2011;Gascon et al, 2011;Lin et al, 2011). A few studies report the negative impact of cord blood PBDEs on levels of human thyroid hormones after in utero exposure (Herbstman et al, 2008;Lin et al, 2011), but most studies conducted in humans have found no correlations.…”
Section: Pbdes and Thyroid Hormonesmentioning
confidence: 99%